The Effect of Location and Price on the Decisions of 2019 Industrial Engineering Students at Bina Nusantara University in Choosing a Printing Outlet - Heruna Tanty; Ferryan Tanly; Sharon Irene Sutikno; Stevia Audrey Efriyanto (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2022)
Printing outlets are frequently-visited outlets by the members of society, especially students, for the purpose of printing documents, photocopies, etc. Large number of printing outlets that can be found today is a dilemma for printing outlet entrepreneurs who are just starting their business. There are several factors that are believed to have an influence on customers’ decisions in choosing a printing outlet, such as outlet location and pricing. The study was conducted to determine the effect of independent variables (location and price) on dependent variables (customer decision). Specifically, 2019 students majoring in Industrial Engineering at Bina Nusantara University will be used as objects of research. Using an online questionnaire, opinions of 124 people were obtained. Various statistical tests were used to process the data, such as descriptive analysis, multiple linear regression model analysis, and hypothesis testing. Results of analysis show descriptive details of data which include maximum, mean, standard deviation, and other values. The results of multiple linear regression model analysis indicate the intercept term is worth 9,496, slope coefficient for location variable is 0,026, and slope coefficient for price variable is 0,143. Hypothesis testing resulted in the conclusion that location and price had no effect, either partially or simultaneously, on the decision to choose outlets by 2019 students majoring in Industrial Engineering at Bina Nusantara University. Therefore, owners or prospective owners of printing outlets targeting 2019 students majoring in Industrial Engineering at BINUS University as customers do not need to consider location and price factors, either partially or simultaneously.